ONCOLOGY NURSE NAVIGATOR PROGRAMME - A NARRATIVE REVIEW - H., Shejila C; Pai, Mamatha S; Fernandes, Donald J (Journal of Health and Allied Sciences NU, 2015)
Introduction: Cancer Care is complex and often requires multiple health care professionals to work in a coordinated and integrated fashion to deliver most effective care available. A team based approach from surgeons, medical oncologists, radiologists, nurse specialists and social worker is required to ensure quality and continuity in care. Specific nursing roles in cancer services are expanding and evolving.Objective: To explore the role of nurse as navigator in oncology care.Methodology: Literature survey was conducted from published journals, text books and online databases (CINAHL, Pubmed, Proquest, Ovid, Medline and Science direct) from January 2000 to January 2014 by using terms pivot nurse ,oncology nurse, case manager, nurse navigator ,patient navigator, oncology nurse navigator along with terms oncology or cancer care.Results: Literature review on nurse navigator programme reveals positive outcomes in various aspects of cancer care, but lack of consensus in study population, intervention settings, outcome measures and methodologies have been noted.Conclusion: Patient navigation using nurses is viewed as an effective strategy to improve standard of oncology care delivered. This review provides evidence that nurse navigator programme can improve specific patient outcomes in cancer care.
Keywords: patient navigation; nurse navigator; cancer care; patient outcomes